An examination of some aspects of the criminal justice system in Nigeria - Wigwe, Chris (African journal of law and criminology, 2015)
The Nigerian criminal justice system is bedeviled and fraught with a plethora of anomalies and institutional/bureaucratic bottlenecks. This stems from the over classification and proliferation of institutions and agencies leading to functional overlap and unnecessary rigidity and delay in the dispensation of justice. The nature of Nigerian criminal justice system calls for a reformative approach to create a balance and strengthen the existing institutions in line with recent practices in other jurisdictions of the world. Nigeria must therefore benefit from and be able to draw a useful lesson from the dynamics that the vagaries of globalization provide in the nature of criminal justice system as practiced in Britain. There are many prosecuting agencies in Nigeria- the Economic and Financial Crimes Commission, Immigration Service, Nigeria Police, the National Drug Law Enforcement Agency, the Code of Conduct Bureau, National Agency for Food and Drug Administration and Control, the Department of State Security (SSS), Custom Service and the Independent Corrupt Practices Commission, with the Nigerian Prison Services playing as host. The procedures adopted by them, though provided in their enabling instruments, have not been consistently followed, leaving room for defence lawyers to diminish the application or enforcement of the substantive matters. This also gives the judges room to venture into the journey of discretional law making.The judicial system has also been altered with advancement in the area of admissibility of electronically generated evidenceby the amendment of the Evidence Act, enactment of Anti Terrorism Act and Cyber.Prohibition Act